2020
DOI: 10.3390/ma13102374
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Wrinkling during Bending of Composite Reinforcement Laminates

Abstract: When a thick laminate is subjected to bending, under certain boundary conditions, wrinkles may appear and develop due to the inextensibility of the fibers. Wrinkling is one of the most critical defects in composite manufacturing. Numerical simulation of the onset and growth of such wrinkles is an important tool for defining optimal process parameters. Herein, several bending experiments of thick laminates are presented. They were found to lead to severe wrinkling and delamination of different kinds. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The manufacturing processes for preforms and prepregs often involve folding or bending of laminates. Depending on the boundary conditions, these bending operations are conducive to the development of wrinkles in the laminate [49,88,89]. It is important to be able to predict the onset and development of these wrinkles through numerical simulations.…”
Section: Analysis Of Wrinkling During Bending Of Multilayer Composite Reinforcementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The manufacturing processes for preforms and prepregs often involve folding or bending of laminates. Depending on the boundary conditions, these bending operations are conducive to the development of wrinkles in the laminate [49,88,89]. It is important to be able to predict the onset and development of these wrinkles through numerical simulations.…”
Section: Analysis Of Wrinkling During Bending Of Multilayer Composite Reinforcementsmentioning
confidence: 99%
“…The lay-up sequence of different layers of multilayer composite reinforcements has a significant influence on the development of wrinkles. Figure 10 shows the experiments and simulations of the deformed shapes of multilayer stack under different orientation of textile reinforcements during the symmetrical bending [89]. As the layers are oriented in [0 • /90 • ] 10 , the inextensibility of fibrous reinforcement results in a large wrinkle during the bending process (Figure 14a).…”
Section: Influence Of the Stack Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…Because the textile reinforcements are thin, some approaches consider them as membrane where the bending stiffness is considered low enough to be neglected [ 36 , 37 , 38 , 39 , 40 , 41 ]. It has nevertheless been shown that the bending stiffness of the textile reinforcement plays an important role in particular on the development of wrinkles [ 14 , 42 , 43 ]. In this article, the objective of the forming simulation is mainly the determination of warp and weft yarns angle variation, which is related to the membrane deformation of the textile reinforcement.…”
Section: Forming Process Simulationmentioning
confidence: 99%